The Effect of Green Accounting and Environment Performance on Sustainable Growth Rate with Profitability as a Moderating Variable - immanuela, intan; Wibisono, Haris; Mujilan (Fakultas Ekonomi Universitas Kadiri, 2025)
Company activity in an effort to maximize profit cannot be separated from the use of natural resources, which are limited in nature and require a considerable amount of time torecover. Companies must be able to manage their finances to obtain profits must also have the ability to minimize the negative impacts of their business activities on society and the environment. In order to maintain a balance between business, environmental, and community interests, companies need to implement green accounting. Based on environmental issues and the importance of sustainable business for companies, the researchers aim to obtain empirical evidence that 1). Green accounting affects the sustainable groeth rate. 2). Environmental performance affects the sustainable growth rate. 3). Green accounting affects sustainable growth rate moderated by profitablility variable. 4). Environmental performance affects the sustainable growth rate moderated by the profitability variable. The study uses a quantitive approach with unit of the analysis being manufacturing companies listed on the Indonesia Stock Exchange (IDX) and participating PROPER from 2020 to 2022. Moderated regression analysis or interaction tests are used in this study. The result of study show that green accounting can negatively affect the sustainable growth rate (SGR) moderated profitability, and profitability cannot moderate the effect of environmental performance on the sustainabile growth rate, Keywords: green accounting, environmental performance, sustainable growth rate.